The Effect Of Tax Planning, Profitability And Deferred Tax Expense On Profit Managementa - amrizal imawan amrizal; Ninik Mas’adah; SITI AZKIYAH NUR FADHILAH; INAYATUS SHOFIYAH (UNIB Press, 2026)
This study aims to analyze the effect of tax planning and tax liabilities on corporate profitability. The study population includes companies in the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange from 2021 to 2023. The research approach used is causality research using quantitative methods and secondary data. The sampling approach used is purposive sampling. This study shows that tax planning, profitability, and tax resilience have a significant effect on earnings management.